2018
DOI: 10.1007/978-3-030-01231-1_30
|View full text |Cite
|
Sign up to set email alerts
|

Affine Correspondences Between Central Cameras for Rapid Relative Pose Estimation

Abstract: This paper presents a novel algorithm to estimate the relative pose, i.e. the 3D rotation and translation of two cameras, from two affine correspondences (ACs) considering any central camera model. The solver is built on new epipolar constraints describing the relationship of an AC and any central views. We also show that the pinhole case is a specialization of the proposed approach. Benefiting from the low number of required correspondences, robust estimators like LO-RANSAC need fewer samples, and thus termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…One AC provides a 2 × 2 affine transformation matrix between the local patches around the corresponding points in two images. Two-view geometry of AC has been investigated [15], [16], [18], [19], and several methods of relative pose from ACs has been proposed [15], [16], [17], [18], [19], [20]. In addition, there are relative pose estimation methods [27], [28], [29] exploit orientation-and scalecovariant features obtained by e.g.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…One AC provides a 2 × 2 affine transformation matrix between the local patches around the corresponding points in two images. Two-view geometry of AC has been investigated [15], [16], [18], [19], and several methods of relative pose from ACs has been proposed [15], [16], [17], [18], [19], [20]. In addition, there are relative pose estimation methods [27], [28], [29] exploit orientation-and scalecovariant features obtained by e.g.…”
Section: Related Workmentioning
confidence: 99%
“…Single camera and ACs: One AC usually provides 3 independent constraints on relative pose [15]. As a result, two ACs are enough to determine the relative pose for a single camera [16], [18], [19] or a single camera with unknown focal length [17]. In [20], guidelines are proposed for effective usage of ACs in the course of a full model estimation pipeline.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows the estimation of a fundamental matrix from 3 ACs [7]. The estimation of a homography and an essential matrix can be accomplished from 2 ACs [32,12,3]. There is an independent work which also uses a single AC to estimate relative planar motion [18].…”
Section: Related Workmentioning
confidence: 99%
“…Baráth et al [3,6] showed that the relationship of ACs and epipolar geometry is linear and geometrically interpretable. Eichhardt et al [14] proposed a method that uses two ACs for relative pose estimation based on general central-projective views. Recently, Hajder et al [19] and Guan et al [18] proposed minimal solutions for relative pose from a single AC when the camera is mounted on a moving vehicle.…”
Section: Introductionmentioning
confidence: 99%